TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE ON THE USE OF DIGITAL TECHNOLOGY IN TEACHING PRACTICE: A COMPARATIVE MODEL IN THE CONTEXT OF INDONESIAN AND MALAYSIA TEACHER PROSPECTIVE STUDENTS (International Conference on Social and Islamic Studies, 2021)
This study examined Indonesian and Malaysian pre-service teachers’ digital technology integration. Technological pedagogical and content knowledge (TPACK) model was utilised to predict the use of digital technology. Three hundred and seventy-seven respondents from two higher education institutions completed a 37-item survey instruments based on the TPACK and digital technology implementation. The establishment of the instruments was conducted through content validity and face validity. The current study results analysed using partial least squares structural equation modelling (PLS-SEM) elaborated 10 significant relationships out of 12 proposed hypotheses. All TPACK domains are related and informed to be a statically valid in explaining digital technology use among the respondents. Policy recommendations and suggestions are offered for the betterment of Indonesian teachers’ level of TPACK and digital technology integration.